Studies on Textile Sludge Treatment Options (Biological Sciences - PJSIR, 2008)
. Analysis of sludge samples of a textile processing factory revealed that the BOD and COD as well as the levels of total solids, nitrogen and phosphorus contents of sludge liquor were high needing treatment before disposal or reuse. Detention time of 60 days was established for aerobic treatment of the sludge. Optimum dosage for physico- chemical methods were established at 4 g/l, using alum and iron III chloride each and 15.5 g/l and 550 mg/l, for lime and polyelectrolyte each. Solids were reduced by 67%, through aerobic and 61% through anaerobic digestion, while the sludge treated by physicochemical method had higher solid content, recording the highest increase with lime.